Quiet luxury : a new sustainability approach or a modern luxury fashion trend? : examining the influence of quiet versus loud luxury on consumer valuations and adoption of luxury fashion brands - Kooli, Kenza (2024)
In the era preceding mass production, individuals possessed considerably fewer clothing and fashion items than in contemporary times. The advent of mass production marked a significant change in the luxury fashion landscape and gave rise to a concern for sustainability, motivated by an expanding recognition of the environmental and ethical challenges associated with the fashion industry. At a time when environmental and social responsibility are paramount, quiet luxury can be a reflection of today's financial climate, unflashy, aesthetically appealing, logo-free, timeless design with high-quality fabrics. Based on previous academic literature, an experimental study was carried out to examine the correlation between the concept of quiet fashion luxury and sustainability, as well as the influence of quiet versus loud fashion luxury on consumer valuations, namely aesthetics, quality, and purchase intention. A moderated-moderation effect of sustainability and conspicuous consumption orientation-CCO was tested on the relationship between the type of fashion luxury (quiet vs. loud) and consumer valuations. Overall results show that quiet and sustainable luxury fashion products are rated more positively than loud and sustainable luxury fashion products. Moreover, moderated-moderation findings show interesting results, which suggest that consumers with high conspicuous consumption orientation levels seem to have higher aesthetic perceptions when exposed to quiet and sustainable luxury fashion products than loud and sustainable luxury fashion products. This research adds a noteworthy and significant contribution to the status, conspicuous consumption orientation, and ethical consumerism literature, highlighting how quiet luxury fashion perceptions are impacted by such traits.